Ayat Ashhabul Kahfi Sebagai Inspirasi Dalam Lukisan Kaligrafi Islami - Mughni Arrifman Agus; Syafei Syafei; Eliya Pebriyeni (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2024)
This work visualizes the verses of the Koran in Surah Al-Kahf which contain the meaning of the story of Ashhabul Kahf in the form of Islamic calligraphy painting and applies painting techniques and sharpens the imagination. The purpose of this work is to preach directly to oneself, appreciators and the general public. The method of creating this work follows five stages, namely: preparation, where the author makes observations and exploration to gain inspiration. Then, at the elaboration stage, relevant references are searched and collected. The third stage, synthesis, involves applying the ideas and main ideas that have been generated. Next, at the concept realization stage, the final work is created based on the previously designed concept. Finally, at the completion stage, the work is exhibited and a report is created that covers the entire process from start to finish. In creating the work, the author uses the Krita application as a technique in creating digital painting works. Each work displays a guitar object consisting of ten works with the title,; "Ashabul Khafi", "Trying to Leave His People", "Greatness of Allah", "Waking Up a Long Sleep", "Promise of Allah", "Number of Ashhabul Kahfi", "Rasulullah SAW", "God willing", "300 + 9", "Say it."